TURTLE HEARING CAPABILITY BASED ON ABR SIGNAL ASSESMENT - Anton Yudhana; Sunardi Sunardi; Jafri Din; Syed Abdullah; Raja Bidin Raja Hassan (Universitas Ahmad Dahlan, 2010)
Sea turtles have existed for millions of years. International Union for Conservation of Nature (IUCN) has reported that the Hawksbill Turtle (Eretmochelys imbricata) is classified as critically endangered. Turtle excluder device (TED) deployment on shrimpnet fisheries is needed for turtle conservation.TED using sound technique is challenge method in fisheries development.The knowledge on turtle hearing capability is limited. The auditory brainstem response (ABR) assessment is method to determine turtle hearing capability. Turtle hearing assessment is basis to design TED. The objective of this paper is to determine turtle hearing cability by analyze its ABR spectral.The subject is Hawksbill turtle with number 2 turtles ie: 3 and 2 years. The measurement was taken at Pusat Pengurusan Penyu (Turtle Management Centre) Padang Kemunting Masjid Tanah Melaka Malaysia. The results shows that turtle 3 years have peak power frequencies 50.78, 101.6, 152.3, 304.7, 355.5, 457, and 507.8Hz respectively whereas the spectral amplitude is ranging 0.03-32.44% spectral. Turtle 2 years has peak power at 457Hz in whole stimulus frequencies while the spectral amplitude is ranging 0.01-2.5% spectral.